Further Studies on Neotropical Epyrini (Hymenoptera, Bethylidae) - Howard E. Evans (Psyche: A Journal of Entomology)
This paper is a supplement to two recent papers published in the Bulletin of the Musem of Comparative Zoology Although these papers were several years in the making, as so often happens they had scarcely appeared when a considerable amount of new material came into my hands. The present paper is concerned with range extensions, notes on variation, and new species in the genera Rhabdepyris, Bakeriella, Calyozina, and Epyris. The abbreviations employed are the same as those used in my two previous papers, but for the sake of ready reference the abbreviations are listed again at the conclusion of this paper.